Simulation Based Performance analysis of Active Clamp DHB ZVZCS Bidirectional DC-DC converter for Low Power Applications - V.V.Subrahmanya Kumar Bhajana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
A novel active clamp dual half bridge DC/DC converter with bidirectional power flow is proposed in this paper and comparative analysis between active clamp DHB ZVZCS and ZVS-ZCS bidirectional DC-DC converter topologies is also presented. By adding active clamping circuits to both bridges, zero voltage and zero current switching are achieved to improve the performance of the bidirectional DC/DC converter. The principle of operation is analyzed and simulated. With the proposed active clamp ZVZCS concept, the MATLAB simulation results of the applications of the fuel cell and battery have been obtained and compared with those of ZVS-ZCS bidirectional converter. The simulation results of proposed converter is compared with the ZVS-ZCS bidirectional DC-DC converter, efficiency, switching losses are the key parameters compared.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.1469